2011
DOI: 10.1002/pits.20615
|View full text |Cite
|
Sign up to set email alerts
|

The use of video self‐modeling with english language learners: Implications for success

Abstract: The efficacy of video self‐modeling (VSM) to improve reading fluency for English language learners (ELLs) is explored. A review of the literature demonstrates the success of VSM in improving non‐ELL students' fluency. Preliminary research with culturally and linguistically diverse students implies that the intervention can be equally effective with these populations. A brief review of second‐language acquisition reveals the ways in which VSM complements the needs of ELLs at various stages of acquisition. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The result is a surge of research related to this approach. Included in that recent influx is research on VSM with stuttering [40], English language learners [38], adult learners and a cooking sequencing task in traumatic brain injury (in addition to existing areas of research described above) [41]. While this is a relatively new area of research in TBI, the approach aligns with current evidence of metacognitive treatment approaches [42][43][44] and Bandura's [45] model of self-learning.…”
Section: Video Self-modellingmentioning
confidence: 58%
See 1 more Smart Citation
“…The result is a surge of research related to this approach. Included in that recent influx is research on VSM with stuttering [40], English language learners [38], adult learners and a cooking sequencing task in traumatic brain injury (in addition to existing areas of research described above) [41]. While this is a relatively new area of research in TBI, the approach aligns with current evidence of metacognitive treatment approaches [42][43][44] and Bandura's [45] model of self-learning.…”
Section: Video Self-modellingmentioning
confidence: 58%
“…Video self-modelling has been used widely in educational settings as a means to facilitate positive behaviours in individuals with autism spectrum disorders, behavioural challenges and second language acquisition [37][38][39]. As stated previously, the focus on positive behaviours in direct video-review of the LCQ aligns with this approach.…”
Section: Video Self-modellingmentioning
confidence: 87%
“…However, we hope that the projects provide information for teachers seeking to integrate culturally responsive instructional strategies and lay the foundations for future research on this strategy. Although VSM has shown promise as a strategy for diverse learners (Ortiz, Burlingame, Onuegbulem, Yoshikawa, & Rojas, ), continued research and systematic research designs need to be employed to establish its efficacy for improving specific learning outcomes for ELLs and SIFE.…”
Section: Resultsmentioning
confidence: 99%
“…The use of authentic tools of all types in foreign language classes has been well-documented. A number of comprehensive reviews of this topic have been published in the past two decades that provide both evidence of its application, and the theoretical underpinnings, in a variety of cultures (see Al-Azri and Al-Rashdi, 2014; Becker and Strum, 2017; Emerick, 2019; Gruba, 2006; Mayer, 1997; McNutty and Lazarevic, 2014; Oritz et al, 2012; Pinner, 2016; Vanderplank, 2010). Research has shown authenticity has a positive impact on classroom outcomes, such as learning tasks (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%